Effect of frozen storage on microbial load of hybrid heteroclarias, Clarias gariepinus and Oreochromis niloticus - Ayeloja, A. A.; Jimoh, W. A.; Shittu, M. O.; Batatunde, B. O. (Journal of Agriculture and Forestry University, 2020)
Effect of frozen storage on microbial load of hybrid Heteroclarias, Clarias gariepinus and Oreochromis niloticus was studied. Fifty samples, each of Heteroclarias, C. gariepinus and O. niloticus with an average weight of 210 + 15g were collected at a commercial fish farm in the study area after which they were processed and frozen at -18°C and microbial analyses were done at 0, 14, 28, 42 and 56 days after frozen storage. Data obtained were logarithmically transformed (log cfu/g) and then subjected to statistical analysis using SPSS 16.0 version. No significant (p>0.05) difference was found for total viable count (TVC), total fungal count (TFC), total coliform count (TCC) and Klebsiella spp. count of the fish species studied during the frozen period. The potential of freezing as a good fish preservation method was established as it inhibited microbial activities thereby elongating fish shelf life. It was concluded that Clarias gariepinus and Oreochromis niloticus fish species can be kept safe up to 56 days by freezing as the microbial loads did not change significantly during the period. Uncontrolled discharge of effluents into the surrounding water bodies should also be checked to avoid contamination prior to fish harvest.